An Epistemological Perspective of Integrated Multidisciplinary Treatment When Dealing With Infertile Women With a Parenthood Goal: The Importance of Matterpsychic Perspective - Vasta, Francesca Natascia; Girelli, Raffaella (Frontiers in Psychology, 2021)
The article proposes a multidisciplinary work perspective integrated with couples who undergo assisted reproductive technology (ART) treatments, with particular attention to the treatment of women. The epistemological references underlying a vision of infertility and sterility that respect the psyche-soma unity of the person are illustrated: the biopsychosocial model, the psychoneuroimmunology and psychosomatic contemporary model of health and illness. Based on clinical experience in a private and institutional setting, the different steps in the course of treatment are described with the related areas of psychological work: from the search for pregnancy, to the choice of adhering to an ART treatment, to conception, up to delivery and beyond. The implications of the work are targeted at a better qualification of psychological interventions in this specific multidisciplinary area.